Acid-base management - is it relevant for the study design of hypothermic neuroprotection? - Frietsch, Thomas; Piepgras, Axel; Krafft, P.; Schwab, Stefan; Kuschinsky, Wolfgang; Waschke, Klaus F. (European journal of anaesthesiology, 2002)
//static.cambridge.org/content/id/urn%3Acambridge.org%3Aid%3Aarticle%3AS0265021502000649/resource/name/firstPage-S0265021502000649a.jpg